Mycobacterium tuberculosis RipA Dampens TLR4-Mediated Host Protective Response Using a Multi-Pronged Approach Involving Autophagy, Apoptosis, Metabolic Repurposing, and Immune Modulation - Shariq, Mohd; Quadir, Neha; Sharma, Neha; Singh, Jasdeep; Sheikh, Javaid A.; Khubaib, Mohd; Hasnain, Seyed E.; Ehtesham, Nasreen Z. (Frontiers in Immunology, 2021)
Reductive evolution has endowed Mycobacterium tuberculosis (M. tb) with moonlighting in protein functions. We demonstrate that RipA (Rv1477), a peptidoglycan hydrolase, activates NFκB signalling pathway and elicits the production of pro-inflammatory cytokines TNF-α, IL-6, and IL-12 through the activation of innate immune-receptor TLR4. RipA also induces enhanced expression of macrophage activation markers MHC-II, CD80, and CD86 suggestive of M1 polarization. RipA harbours LC3 motifs known to be involved in autophagy regulation and indeed alters the levels of autophagy markers LC3BII, P62/SQSTM1 along with an increase in the ratio of P62/Beclin1 - a hallmark of autophagy inhibition. Use of pharmacological agents rapamycin and bafilomycin A1, reveals that RipA activates PI3K-AKT-mTORC1 signalling cascade that ultimately culminates in the inhibition of autophagy initiating kinase ULK1. This inhibition of autophagy translates into efficient intracellular survival, within macrophages, of recombinant M. smegmatis expressing M. tb RipA. RipA which also localizes into mitochondria inhibits the production of oxidative phosphorylation enzymes to promote a Warburg-like phenotype in macrophages that favours bacterial replication. Furthermore, RipA also inhibited caspase-dependent programmed cell death in macrophages thus hindering an efficient innate antibacterial response. Collectively, our results highlight the role of an endopeptidase to create a permissive replication niche in host cells by inducing repression of autophagy and apoptosis along with metabolic reprogramming and point to the role of RipA in disease pathogenesis.